Development and Validation of the Coeliac Disease Food Attitudes and Behaviours Scale. (19th August 2018) - Satherley, Rose-Marie; Howard, Ruth; Higgs, Suzanne
Abstract : Objectives . Previous studies on coeliac disease suggest that attitudes towards the gluten-free diet may contribute to the development of disordered eating. This study describes the development and validation of the Coeliac Disease Food Attitudes and Behaviours scale (CD-FAB) to measure these behaviours in coeliac disease. Research Methods and Procedures . Focus groups were used to develop 33 potential questionnaire items. These items were reviewed by service users and then distributed online to 157 adults with coeliac disease. Items were removed based on ceiling/floor effects, high interitem correlations (>0.7) and factor analysis. 11 items were retained. Exploratory factor analysis was then conducted. The psychometric properties of the final version of the CD-FAB were assessed via using an online platform. Results . The CD-FAB had 11 items distributed across one factor assessing attitudes and behaviours towards food. These factors explained 44.1% of the variance in responding. The CD-FAB and its subscales had high internal consistency (Cronbach's alpha > 0.7) and psychometric validation indicated good convergent and discriminant validity. High scores on the CD-FAB are associated with psychological distress and an impaired quality of life. Conclusions . The CD-FAB is a reliable and valid measure of food attitudes and behaviours in coeliac disease. As a new disease-specific instrument, it may be a useful tool for evaluating food concerns in individuals with coeliac disease in a clinical setting and for further exploring the development of disordered eating patterns in coeliac disease. Further research is required to assess the full potential of the CD-FAB.